Implementasi Peraturan Daerah Nomor 9 Tahun 2018 Tentang Ketertiban Umum dan Ketentraman Masyarakat Mengenai Tertib Kebersihan pada Kecamatan Amuntai Tengah Kabupaten Hulu Sungai Utara - Hidayatullah, Gusti Muhammad; Paridati, Paridati (SENTRI: Jurnal Riset Ilmiah, 2025)
The purpose of this study is to determine the implementation of regional regulations and the factors influencing the enforcement of public order and community tranquility related to cleanliness compliance in Amuntai Tengah District, Hulu Sungai Utara Regency. This research employs a qualitative descriptive approach with data collected through observation, interviews, and documentation. Informants were selected using purposive sampling, totaling 19 individuals. The collected data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The findings show that the implementation of the regional regulations has been carried out well. In terms of environmental conditions, the socio-cultural environment indicator and recipient involvement are still considered less satisfactory. Regarding inter-organizational relations, coordination with relevant agencies remains suboptimal, although the indicators of sanctions and supervision fall into the fairly good category. Organizational resources, both human and non-human, are evaluated as good. Additionally, the characteristics and capabilities of implementing agents are also assessed as good, based on the bureaucratic structure, norms, and relationship patterns. Supporting factors in policy implementation include the availability of human resources, non-human resources, bureaucratic structure, norms, and relationship patterns, while the inhibiting factors consist of the community’s socio-cultural environment and the less optimal inter-agency coordination.